Pengaruh Tindakan Kekerasan Orangtua Terhadap Kesehatan Mental Anak - Amran, Ali (FDIK IAIN Padangsidimpuan, 2021)
There are social facts in the form of acts of violence against parents to their children when they provide education. Likewise the facts was found in this risearch that there are acts of violence committed by parents against children in the process of educating, that are carried out repeatedly both physically, hitting, kicking, pinching, pushing, twisting, and slapping. Likewise, acts of violence are emotionally treated against children, in Silayang Village, Ranah Batahan District, West Pasaman Regency. Acts of physical and emotional violence are very influential on mental health so that children have mental disorders or mental health.